A new species of xestospongia (porifera: demospongea), from the colombian caribbean (1983)
Xestospongia rosariensis is named from coral reef habitats of the Nuestra Señora del Rosario Archipelago in the Colombian Caribbean. This sponge is tube-shaped, brown in color, hard and brittle in consistency, and is provided with sinous surface irregularities. The dense skeleton reticulation of thick spicule tracts is typical for the genus. Spicules are oxea having mean dimensions of 183.6 x 9.4 µm. X. rosariensis has several affinities with X. subtriangularis, particularly the small dimensions of spicules.  Its distintive growth form makes the new species unmistakable among the members of Xestospongia.